The role of Jahn–Teller distortion in insulator to semiconductor phase transition in organic–inorganic hybrid compound (p-chloroanilinium)2CuCl4 at high pressure. Issue 48 (18th November 2015) - Ghalsasi, Pallavi; Garg, Nandini; Deo, M. N.; Garg, Alka; Mande, Hemant; Ghalsasi, Prasanna; Sharma, Surinder M.
Abstract : The captions for pressure values are not centered below each micrograph. Abstract : ( p -Chloroanilinium)2 CuCl4 (C2 H14 Cl6 CuN2 ) is from an important family of organic–inorganic layered hybrid compounds which can be a possible candidate for multiferroicity. In situ high pressure FTIR, Raman and resistivity measurements on this compound indicate the weakening of Jahn–Teller distortion and the consequent removal of puckering of the CuCl6 4− octahedra within the layer. These effects trigger insulator to semiconductor phase transition along with a change in the sample colour from yellow to dark red. This article explains the crucial role of the anisotropic volume reduction of the CuCl6 4− octahedron (caused due to the quenching of Jahn–Teller distortion) in the observed insulator to semiconductor phase transition.